Modeling longitudinal data - Weiss Robert E (New York Springer-Verlag, 2005)
This book teaches the art and statistical science of modern longitudinal data analysis. The author emphasizes specifying, understanding, and interpreting longitudinal data models. He inspects the longitudinal data graphically, analyzes the time trend and
Keywords: Data analysis; Longitudinal data